Enhanced Impulsive Action Selection in Middle-Aged Adults—Insights From an Oculomotor Simon Task - Duprez, Joan; Houvenaghel, Jean-François; Argaud, Soizic; Naudet, Florian; Dondaine, Thibaut; Auffret, Manon; Robert, Gabriel; Drapier, Dominique; Vérin, Marc; Sauleau, Paul (Frontiers in Aging Neuroscience, 2016)
Several studies have investigated the age-related impact in cognitive action control. However, to our knowledge, none has focused on the effect of moderate age on the strength of automatic activation according to the activation suppression model. We therefore investigated the effect of moderate age on cognitive action control using an oculomotor version of the Simon task and distributional analyses. A group of middle-aged (n = 39; 57 ± 9 years) healthy adults was compared to a group of young healthy participants (n = 43; 24 ± 3 years). We first analyzed the overall impact of age on the congruence effect and then used conditional accuracy functions and delta plots to assess the strength of automatic activation and selective inhibition respectively. Compared to young participants, middle-aged participants showed a greater congruence effect as well as higher rates of fast errors in conflict situations indicating an enhanced impulsive action selection. Furthermore, the overall downward slope of the congruence effect’s evolution was significantly steeper in older participants and the last slope tended to be significantly steeper. This may indicate that the middle-aged participants exerted a stronger selective inhibition. Our results suggest that middle-aged adults are more prone to impulsive action selection than young adults. Recent theories postulate that older adults might implement compensatory mechanisms to supply cognitive difficulties. This is in line with our results suggesting a potential greater selective inhibition. Overall, this study proposes that moderate aging impacts both processes of impulsive response selection and suppression underlying cognitive action control.